Perancangan Sistem Informasi Penjadwalan Mata Kuliah Dan Penentuan Ruang Kosong Menggunakan Metode Waterfall - FERDINAL R (DEPATI PARBO PRESS, 2018)
ABSTRACT The problem of lecture scheduling is one of the hardest cases if solved using manual methods. Problems in scheduling courses are usually associated with constraints where the course may have several classes, a lecturer can take more than one course, teaching hours up to the determination for the execution of additional lectures. In this journal Waterfall method is used to develop a software that is sequential that workmanship of a system done in sequence or in linear. So if step one has not been done then 3 will not be able to do step 2, 3 and so on. Automatically the 3rd stage will be done if the first and second stages have been done. Keywords: Scheduling, Waterfall, Course.